Serum cortisol measurement in comparison between dexmedetomidine and fentanyl for sympathetic attenuacion during intubation. - Yip Kin, Soon (2011)
Several drugs have been used to attenuate the stressor response to endotracheal intubation .This study is to compare the sympathetic attenuation response of dexrnedetornidine versus fentanyl for endotracheal intubation as a sympatholytic by measuring differences in pre- and post-induction serum cortisol and hemodynamic parameters This is a prospective, single blinded, randomized clinical trial with 100 patients scheduled for elective surgery under general anesthesia, ASA class I-II were selected and divided equally into 2 groups. All patients were given a premedication dose of midazolam and serum cortisol levels pre-induction of general anesthesia were taken. Pre-induction of general anesthesia is defmed as the time when the patients arrive at the operation theatre before any induction agents for general anesthesia are given. The test group received a loading dose of dexmedetomidine 10 meg/kg over 10 minutes, followed by a titrating dose of propofol and rocuronium 0.6 mg/kg. Post intubation, serum cortisol was resampled. The control group received a bolus dose of fentanyl 2 meg/kg, propofol 2 mg/kg and IV rocuronium 0.6 mglkg for intubation, and also had their post-intubation serum cortisol recorded. The dexmedetomidine group recorded a reduction in serum cortisol levels of 21.61 °/o postinduction compared to a reduction of only 2.1 °/o for the group receiving fentanyl (p 0.003). Dexmedetomidine group recorded a mean decrease in serum cortisol post-induction of 103.56 nmoVL, standard deviation 139.61 and the group given fentanyl having a mean reduction of 9.308 nmol/1, standard deviation 169.52. Hemodynamic parameters showed a decrease in the fentanyl group compared to the dexmedetomidine, with a decrease in MAP of 19.07% compared to 12.65% in the dexmedetomidine group (p 0.042). Dexmedetomidine and fentanyl are both safe drugs with sedative, analgesic and sympatholytic effects. In this study, dexmedetomidine has been shown that it can also potentially be utilized as an adjunct to laryngoscopy and intubation. Hemodynamic stability is well maintained with dexmedetomidine, and sympatholysis is possibly superior compared to fentanyl during intubation.